The Politics of Criminal Law in Tackling Crimes Under the Guise of Electronic Investment in Indonesia - Manullang, Herlina; Habeahan, Besty; Nduru, Idarniman (UNES Law Review, 2023)
Criminal law politics is indispensable in tackling crimes under the guise of electronic investment to overcome the rampant crime in the field of information technology. The Criminal Code, Consumer Protection Law has not been able to overcome information technology crimes, then the government issued Law No. 19 of 2016 concerning Electronic Information and Transactions as an anticipatory step against the negative impact of advances in information technology. The cyber world has great crime potential and is very difficult to catch because most of the people present in cyberspace are fictitious. Countermeasures carried out by the government in tackling crimes under the guise of electronic investment are still oriented towards the criminal justice system, by applying the provisions in Law No. 19 of 2016 concerning Electronic Information and Transactions. Countermeasures faced by law enforcement in tackling crimes under the guise of electronic investment include, lack of law enforcement officers savvy with technology, limited facilities and infrastructure, and lack of public investment skills.